Exploring the effects of light and sleep deprivation on the chromatin structure and transcriptional landscape of specific brain regions - Walsh, SP (2021)
Disruption to normal circadian rhythms and frequent periods of sleep deprivation (SD), are endemic in today’s 24 hour society; therefore understanding the fundamental biology underlying what happens in the suprachiasmatic nuclei (SCN) during entrainment, and other specific brain regions following SD has never been more important. Current understanding of entrainment and SD within the SCN at the molecular level is still very limited, despite SD already having been shown to have a profound effect on brain function.